In-game physiological responses of young elite male and female golf players: A field based study - GERÇEK, NEJLA (My University, 2022)
Background. Females\" golf course lengths have been reduced due to their strength characteristics, leading to shorter shot distances than men. Although the golf game requires different physical conditions for females and males, the physiological demands of both genders are unknown. Objectives. This study aimed to investigate the physiological responses of female and male golfers during 18 holes golf games. Methods. Twenty-nine elite golf players (females:11, males:14) with 1-10 handicaps participated in the study (age: 17.76 +/- 2.05 years and handicaps: 5.4 +/- 2.9). The players\" physiological responses were assessed using BioHarness 3 Zephry wireless supported heart rate monitor. Perceived exertion rates of the players were enrolled using Borg Scale. Results. Female golf players had significantly higher heart rate values and energy expenditures than male golf players during 18 holes golf games (P0.05). Conclusion. Although the golf game is facilitated by changing the course length for female golf players, it has been investigated that they encountered greater physiological demands than males. However, the perceived exertion rates of females were similar to those of males during the golf course play. This study provides a comprehensive insight into the physiological demands of female and male golf players during 18 holes golf games. It can be suggested that female players should not compete in the same category as male players, despite the game being simplified by changing the course length.
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC); Heart Rate; Golf Play; Energy Expenditure; Rate of Perceived Exertion; PERCEIVED EXERTION; ENERGY-EXPENDITURE; HEART-RATE; EXERCISE; BLOOD